Effect of Nutritional Health Program in Improving the Quality of Life-of Patients with Chronic Renal Failure in Hemodialysis Center of Duhok City - Miaad Hussein Kadhim; Alaa Noori Sarkees; Khalida Elias Georgies (College of Nursing,University of Mosul, 2016)
Background and aim: Patients with chronic kidney failure are vulnerable of cognitive impairment. That's why they become more users of pharmacological products and develop comorbidities such as hypertension and diabetes. Therefore, nutritional therapy constantly considered a major feature of Chronic Kidney Failure management. So, the nutritional therapy aimed to attainment the control both metabolic and fluid as well as prevention and correction of signs, symptoms and complications of progressed Chronic Renal Failure. The present study aimed to investigate the effectiveness of the education nutritional health program in improving the quality of life of patients with chronic renal failure. Materials and method: The present Quazi-experimental study was conducted in hemodialysis center and renal transplantation department in Azadi teaching hospital, from February 15, 2015 through March 1, 2016. The sample of the study was consisted of (30) Non-probability (purposive) patients with chronic renal failure. Data were collected through using questionnaire related to health education nutritional program before and after its application upon patients with chronic renal failure. Analysis of data performed through the application of descriptive data (Frequency and percentage) and inferential data of (T. test) employed statistical application. Results: The findings of the study had revealed that the experimental group had benefited of the program as supported by their nutritional health-related knowledge improvement. Furthermore, the result indicated that the highly significant differences between pre and post educational intervention regarding patients level of physical and psychological quality of life. Conclusion: The health education nutritional program was confirmed its effectiveness throughout the study, the findings can be interpreted so that the group had benefited from the health education nutritional program and evidenced improvement in their knowledge related to nutritional behavior and quality of life. Recommendation: The study recommended that the Ministry of Health in Kurdistan Region of Iraq should sponsor the health education nutritional program to be applied by nephrology nurses in hemodialysis centers considering its potential addressing patients' specific needs and problems. Keywords: Nutritional Health Program, Quality of Life, Chronic Renal Failure.